Леся Українка і Марія Конопницька (порівняльно-типологічне зіставлення) - Булаховська, Ю. (Слово і Час, 2010)
У статті порівнюються образи й мотиви в поезії української і польської письменниць. Їхня спільність
убачається в пафосі боротьби, вірі в силу художнього слова, увазі до фольклору, зверненні до античних
образів, до закордонної тематики. The article juxtaposes the metaphors and motifs used in the poetic works of L. Ukrayinka and M. Konopnicka
in order to show the solidarity of both female writers in struggling against unfavourable social conditions as
well as obvious affinities concerning their belief in the power of poetry, their use of folkloric elements, and their
treatment of antique metaphors and foreign factual material. В статье сопоставляются образы и мотивы украинской
и польской писательниц. Их общность усматривается
в пафосе борьбы, вере в силу художественного слова,
внимании к фольклору, обращении к античным образам
и заграничной тематике.